(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
Heart rupture is a particularly serious clinical condition and is characterized by a high mortality rate. This pathology is usually rare and is more likely to affect older women. It often follows as a complication of a myocardial infarction and the subsequent symptomatology is stackable to that of heart failure or cardiogenic shock. In the reported clinical case, the acute heart rupture occurred in correspondence with the free wall of the right ventricle, rapidly causing an important cardiac tamponade with an unfavorable course.